Assisting the Use of AI in Journalism through a Verification-Journalism Approach (Oratio Directa, 2024)
Journalism is a profession that is always in contact with technology. Along with the development of telecommunications technology, journalism has changed its production processes by using artificial intelligence (AI). Although AI offers various conveniences, it still has weaknesses and must be used cautiously because inaccurate data can produce information bias. The public may consume incorrect news and consequently develop incorrect perceptions and behavior. Verification journalism can reduce information bias in work produced by journalists using AI assistance. Its principles require journalists to remain careful and to prioritize ethics and truth in journalistic work.
Keywords: Artificial intelligence; Verification journalism; Journalistic ethics; Information bias; News production